Зависимость длительности развития гусениц различных популяций восклицательной совки (Agrotis exclamationis L.) от температуры и светового режима - Ахмедов, Р.М. (Вестник зоологии, 1972)
The effect of a temperature of 15, 18 and 25°C at light day from 0 to 24 hrs was investigated as applied to duration of Agrofis exclamations L. caterpillar development.
The Azerbaijan, Belgorod, Perm and Leningrad populations were investigated from four geographical points with strongly differing climatic conditions.
The results of the experiments show that dependence of the caterpillar development aclivity on photoperiodic conditions is most distinctly pronounced at low temperatures
(15 and 18° C).